Hubungan Kualitas Layanan Pada Aplikasi Mobile JKN Terhadap Tingkat Kepuasan Pengguna Fitur Antrean Online 2025 - Zaif Muftahifa; Andreas Kurnianto; Masruchi (STIKES Ngesti Waluyo, 2025)
This study is based on the problem that many people have not yet used the Mobile JKN application, particularly the online queue feature. According to several users, the reasons for not using the application include its susceptibility to system errors and its complexity, which make them more comfortable with the manual system than adopting an innovative one. This study aims to determine the relationship between service quality and user satisfaction with the Mobile JKN application, specifically the online queue feature. In addition, this study seeks to identify which service quality indicators (reliability, efficiency, fulfilment, privacy, and responsiveness) have the greatest influence on user satisfaction. This research employed a quantitative, cross-sectional design. The sample of this study were patients in Parakan community health centres who ever used Mobile JKN, as many as 100 respondents. Based on the study results, the Spearman Rank correlation analysis conducted with a computerized system yielded a calculated correlation coefficient (r_calculated) of 0.502 and a significance value (p) of 0.00. Since r_calculated > r_table (0.502 > 0.1966), it can be concluded that there is a positive and significant relationship between the service quality of the Mobile JKN application and the level of user satisfaction among the users of online queue feature at Parakan Primary Health Care Center, with a moderately strong correlation. Furthermore, the linear regression analysis revealed that the service quality indicators that significantly influenced user satisfaction were efficiency and responsiveness, with significance values of 0.001 and 0.017, respectively.